Financial incentives for smoking cessation in pregnancy: randomised controlled trial. (27th January 2015) - Tappin, David; Bauld, Linda; Purves, David; Boyd, Kathleen; Sinclair, Lesley; MacAskill, Susan; McKell, Jennifer; Friel, Brenda; McConnachie, Alex; de Caestecker, Linda; Tannahill, Carol; Radley, Andrew; et al.
Abstract : Objective To assess the efficacy of a financial incentive added to routine specialist pregnancy stop smoking services versus routine care to help pregnant smokers quit. Design Phase II therapeutic exploratory single centre, individually randomised controlled parallel group superiority trial. Setting One large health board area with a materially deprived, inner city population in the west of Scotland, United Kingdom. Participants 612 self reported pregnant smokers in NHS Greater Glasgow and Clyde who were English speaking, at least 16 years of age, less than 24 weeks pregnant, and had an exhaled carbon monoxide breath test result of 7 ppm or more. 306 women were randomised to incentives and 306 to control. Interventions The control group received routine care, which was the offer of a face to face appointment to discuss smoking and cessation and, for those who attended and set a quit date, the offer of free nicotine replacement therapy for 10 weeks provided by pharmacy services, and four, weekly support phone calls. The intervention group received routine care plus the offer of up to £400 of shopping vouchers: £50 for attending a face to face appointment and setting a quit date; then another £50 if at four weeks' post-quit date exhaled carbon monoxide confirmed quitting; a further £100 was provided for continued validated abstinence of exhaled carbon monoxide after 12 weeks; a final £200 voucher was provided for validated abstinence of exhaled carbon monoxide at 34-38 weeks' gestation. Main outcome measure The primary outcome was cotinine verified cessation at 34-38 weeks' gestation through saliva (<14.2 ng/mL) or urine (<44.7 ng/mL). Secondary outcomes included birth weight, engagement, and self reported quit at four weeks. Results Recruitment was extended from 12 to 15 months to achieve the target sample size. Follow-up continued until September 2013. Of the 306 women randomised, three controls opted out soon after enrolment; these women did not want their data to be used, leaving 306 intervention and 303 control group participants in the intention to treat analysis. No harms of financial incentives were documented. Significantly more smokers in the incentives group than control group stopped smoking: 69 (22.5%) versus 26 (8.6%). The relative risk of not smoking at the end of pregnancy was 2.63 (95% confidence interval 1.73 to 4.01) P<0.001. The absolute risk difference was 14.0% (95% confidence interval 8.2% to 19.7%). The number needed to treat (where financial incentives need to be offered to achieve one extra quitter in late pregnancy) was 7.2 (95% confidence interval 5.1 to 12.2). The mean birth weight was 3140 g (SD 600 g) in the incentives group and 3120 (SD 590) g in the control group (P=0.67). Conclusion This phase II randomised controlled trial provides substantial evidence for the efficacy of incentives for smoking cessation in pregnancy; as this was only a single centre trial, incentives should now be tested in different types of pregnancy cessation services and in different parts of the United Kingdom. Trial registration Current Controlled Trials ISRCTN87508788 .